Liburnians and Illyrian lembs : Iron Age ships of the Eastern Adriatic - Boršić, Luka, (Archaeopress Archaeology, 2021)
This title explores the origins of two types of ancient ship connected with the protohistoric eastern Adriatic area: the 'Liburnian' and the Southern Adriatic 'lemb'. An extensive overview of written, iconographic and archaeological evidence questions the existing scholarly assumption that the liburna and lemb were closely related.